Prevalence of Serum Antibodies against Six Leptospira Serovars in Buffaloes in Tabriz, Northwestern Iran - Mohammad, Tolouei (Journal of Buffalo Science, 2014)
Leptospirosis is an important zoonotic infectious and its prevalence is unknown in buffalo in Iran particularly in Tabriz, northwest of the country. To survey the prevalence of Leptospira infection in buffaloes in Tabriz, blood samples were collected from 85 female buffaloes slaughtered in Tabriz industrial slaughterhouse from December 2008 to November 2009. Sera were stored at -20°C until they were examined. Sera were initially screened at serum dilution of 1:100 against six live antigens of Leptospira interrogans, Pomona, Canicola, Hardjo, Ballum, Icterohaemorrhagiae and Grippotyphosa by using the microscopic agglutination test (MAT).The samples were considered positive if 50% or more of agglutination of leptospire in a dilution tests serum of l:100 were observed. 30 serums (35.29%) at dilution 1:100 were positive against 1 or 2 of serovars. the highest prevalent serovar in buffalo was Grippotyphosa (51.3%), and fallowed whit Pomona (29.7%), canicola (10.8%) and Icterohaemorrhagiae (8.1%). All of the samples were seronegative for serovar Ballum and Hardjo. Statistical analysis of the results showed that the rates of the infection in the autumn-winter and spring–summer didn’t have significant difference (p > 0/05). The rate of the infection has been statistically increased with the aging (p<0/05) and the animals with 3 and 4 pair’s permanent teeth had the highest infection rates. The serological infection rate in buffaloes in Tabriz is relatively high and it appears that it is because of living type of buffaloes in water and swamp, thus consequently the preventive methods must be applied to control of the disease.